PROBLEMATIQUE D’ UNE ENQUETE PREALABLE DANS L’ACQUISITION DES TERRES RURALES EN REPUBLIQUE DEMOCRATIQUE DU CONGO FACE A LA DECENTRALISATION - Jean Pierre LITEMA YENI ,; Lucien MUKONKOLE KADIOBO, (IJRDO - Journal of Social Science and Humanities Research, 2020)
The present survey appears in the setting of the matters of procedure of acquirement of the farming or customary earths in Democratic Republic of Congo.    And of this fact, she/it aims to demonstrate the difficulty and even the incoherence that rages currently himself in the application of the law n° 73-021 of July 20 1973 structural general régime of goods, fundamental and real estate régime and régime of the safeties as modified and completed by the law n° 80-008 of July 18, 1980, that indicates and precise the authorities that must intervene in the setting in work of the procedure of the previous investigation for the transfer of the farming earths; screw to - screw of the law organic n° 08/016 of October 07, 2008 carrying composition, organization and working of the Territorial Entities Decentralized and their reports with the state and the Provinces, that as for her, suppressed in the administrative configuration the existence of the commissioners of distinct that, according to the mind of the law n° 73-021 of July 20, 1973 above quoted, the commissioners of districts are the only authorities authorized to open the previous investigation before she/it is done by the Administrators of the territories